Diagnostic Errors in Pediatric Echocardiography Development of Taxonomy and Identification of Risk Factors - Benavidez, Oscar J. (Circulation, 2008)
BACKGROUND: Despite increased interest in complications within pediatric cardiology, the domain of imaging-related diagnostic errors has received little attention. We developed a new taxonomy for diagnostic errors within pediatric echocardiography that categorizes errors by severity, preventability, and primary contributor. Our objectives were to examine its findings when applied to diagnostic error cases and to identify risk factors for preventable or possibly preventable diagnostic errors. METHODS AND RESULTS: Diagnostic errors were identified at a high-volume academic pediatric cardiac center from December 2004 to August 2007. Demographic, clinical, and situational variables were collected from these cases and controls. During the study period, ≈50 660 echocardiograms were performed. Among the 87 diagnostic error cases identified, 70% affected clinical management or the patient was at risk of or experienced an adverse event. One third of the errors were preventable and 46% were possibly preventable; 69% of preventable errors were of moderate severity or greater. Univariate analysis demonstrated that preventable or possibly preventable errors were more likely to involve younger patients, lower body weight, study location, sedated/anesthetized patients, studies performed and interpreted at night, uncommon diagnoses, and greater anatomic complexity than controls. Multivariate analysis identified the following risk factors: rare or very rare diagnoses (adjusted odds ratio [AOR], 9.2; P<0.001), study location in the recovery room (AOR, 7.9; P<0.001), moderate anatomic complexity (AOR, 3.5; P=0.004), and patient weight <5 kg (AOR, 3.5; P=0.031). CONCLUSIONS: A diagnostic error taxonomy and knowledge of risk factors can assist in identification of targets for quality improvement initiatives that aim to decrease diagnostic error in pediatric echocardiography.